Pengaruh Penyimpanan Bahan Makanan Perishable Terhadap Kualitas Bahan Makanandi Kitchen Cambridge Hotel Medan - Nazmi, Sabrina (Tourism, Hospitality And Culture Insights Journal, 2023)
Utilising food storage is necessary to decrease waste and increase food quality. In this study, the effect of tainted food storage on its quality was evaluated at the Cambridge Hotel Medan. 35 people gathered to hear the announcement. Quantitative techniques using a Likert scale and inferential statistics like validity, reliability, simple regression, and determination are included in data analysis. The Statistical Package for Social Science (SPSS) version 25 was used for the analysis. The study's findings revealed that, according to the determination test, the Cambridge Hotel Medan's food storage had a 12.6% influence on quality, while other factors outside the study had an 87.4% impact. With a significance level of 0.037, the sum of the t values (2,180) exceeds the table of the t values (2.036). The Ha hypotheses are therefore accepted, and the H0 hypothesis is disproved. According to the Ha hypothesis, there is a direct correlation between the integrity of food and how it is stored. Food and beverage goods must be further trained and supervised at storage in line with Standard Operating Procedures (SOP) in order to reduce food waste.